Synthesis and Characterization of Novel (Z,E)-vic-dioximes and their Transition Metal Complexes - Sarikavakli, Nursabah; Tuba Cakici, Hikmet (Asian Journal of Chemistry, 2012)
Three novel vic-dioxime ligands containing the hydrazone group, (1Z,2E)-2-(hydroxyimino)-N'-[(1E)-(4-hydroxyphenyl)methylene] ethanehydroximohydrazide, (L1H2), (1Z,2E)-N'-[(1E)-(2,3-dihydroxyphenyl)methylene]-2-(hydroxyimino)ethanehydroximohydrazide, (L2H2), (1Z,2E)-2-(hydroxyimino)-N'-[(1E)-(2-hydroxy-3-methoxyphenyl)methylene]ethanehydroximohydrazide, (L3H2) and their Ni(II) and Cu(II) complexes have been synthesized. All the metal complexes were prepared under similar conditions from the ligands and the corresponding metal salts by addition of a strong base. Ni(II) and Cu(II) complexes of the ligands have a metal:ligand ratio of 1:2 and the ligands coordinate through the two N atoms, as do most of the vic-dioximes. The synthesized compounds are characterized by the techniques such as elemental analyses, molar conductance measurements, magnetic susceptibility measurements, UV-VIS, FT-IR, 13C NMR, 1H NMR and thermogravimetric analyses (TGA). The measurements of molar conductance show that all the complexes are non-electrolytes.